Subjective well-being of university undergraduate students - Velasquez, Zisa dela Merced (2007)
The research is a two-phase sequential explanatory mixed method design to investigate the subjective well-being of Filipino university undergraduate students. Subjective well-being represents how and why people evaluate their life which includes happiness, pleasant emotions, life satisfaction, and a relative absence of unpleasant moods and emotions. Results of the study showed that gender and living conditions are related to University students' experiencing high levels of positive emotions, friends, family, being able to do things one enjoys, and satisfaction of basic needs are the factors that mostly contribute to their subjective well-being.